Can we say [ ( -24 ) ÷ 4 ] ÷ ( -2 ) = ( -24 ) ÷ [ 4 ÷ ( -2 ) ] ?

### 2 thoughts on “Can we say [ ( -24 ) ÷ 4 ] ÷ ( -2 ) = ( -24 ) ÷ [ 4 ÷ ( -2 ) ] ?”

### Leave a Comment

You must be logged in to post a comment.

Can we say [ ( -24 ) ÷ 4 ] ÷ ( -2 ) = ( -24 ) ÷ [ 4 ÷ ( -2 ) ] ?

You must be logged in to post a comment.

Answer:21 is the answer

LHS is not equal to RHS

Step-by-step explanation:[ ( -24 ) ÷ 4 ] ÷ ( -2 ) = ( -24 ) ÷ [ 4 ÷ ( -2 ) ]

( -6 ) ÷ (-2) = (-24) ÷ (-2)

3 = 12

LHS is not equal to RHS